(untitled) (Journal of Fiber Bioengineering and Informatics, 2018)
In order to make bra cups meet the needs of female customers, as well as to enhance the efficiency of designing bra products, this paper made a study on the definition of digital moulded bra cup moulding features and parametric modeling by means of parametric features design. The study introduced the concepts of moulded bra cup's shape features and then defined the same. The instructional effects of female breast shape features and size features being involved in designing of moulded bra cups were analyzed. The relationship between the shape features and size features of breasts and the shape features of moulded bra cups were also discussed. Meanwhile, the study made a parametric presentation on the feature points and feature curves of moulded bra cups. It realized that parametric modeling should aim at feature points and curves. The processes of modeling of digital moulded bra cup were mentioned, and were made more visualized adhering to human's designing principles, which enhancing the efficiency of developed moulded bra cup products.